Difficulties and Achievements: formation of Siberian Directorate of Military Educational Institutions of the Red Army (1919–1920) - I. V. Fedotova (Омский научный вестник: Серия "Общество. История. Современность")
The article described a little-studied aspect of Soviet military construction in Siberia at the final stage of the Civil War in Russia — the creation and the first months of the activity of the Siberian Directorate of Military Educational Institutions of the Red Army. The source base of the study is unpublished materials of the office work of Siberian Revolutionary Committee, the Omsk press and memoirs. The theoretical basis of the study is a combination of anthropological and systemic approaches, problem-chronological, comparative-historical and biographical methods. The author comes to the conclusion about the key role of the Soviet military leaders M. N. Tukhachevsky and N. I. Koritsky in the formation of a network of military schools in Siberia, and the influence of the Siberian Directorate of Military Educational Institutions on the development of military education in the region and the cultural level of the local population.